The Gender Perspective Of Psychological Challenges Experienced By Residents In Homes For The Aged In Nigeria - Osakwe-Ogo, Winifred Uju (Archives of Business Research, 2019)
The purpose of the study was to identify the gender differentials in psychological problems experienced by residents of homes for the aged in Nigeria as well as the strategies for reducing the problems. Two research questions and two hypotheses guided the study. The design was descriptive, involving 235 residents of mission and government-managed homes for the Old selected through cluster random sampling. Data were collected through a 108 item research-developed questionnaire organized in four sections. Mean ratings were used in answering the research questions, while t-test statistic was used in testing the hypotheses at 0.05 level of significance. Findings indicated that residents of old people’s homes experience a series of psychological challenges such as depression, insomnia, amnesia, emotional problems and fear. While, female residents rated emotional challenges and fears as more contributory to their psychological challenges and male respondents rated self-esteem as significant influencers to psychological challenges. In addition, the residents perceived that policy enforcement, pension policies and medical services as key strategies to reducing psychological challenges and that resident of mission-managed homes rated their experiences of social problems more than the residents in government managed homes. Based on this a number of recommendations were made which include; policy review of existing policies on the care of the aged in the society, pension administration review, more participation by the Nigerian government, re-training and employment of care-givers by non-governmental bodies, missionary and the government, integrating a gender based approach in counseling, ensuring adequate medical facilities are available, fast tracking medical response services to members of this elite group.